Encyclopedia of distance learning - Howard, Caroline, 1953-; Thomson Gale (Firm) (Hershey, Pa. : Idea Group Reference, 2005)
"This encyclopedia offers the most comprehensive coverage of the issues, concepts, trends, and technologies of distance learning. More than 450 international contributors from over 50 countries"--Provided by publisher.
v. 1. A-C -- v. 2. D-H -- v. 3. I-Q -- v. 4. R-Z
Includes bibliographical references and indexes.
Electronic reproduction.
Keywords: Distance education -- Encyclopedias; e-knihy online; e-books online